The Effect of Brand Image, Price, and Marketing Content on Buying Interest of Erigo Products in Surabaya - Bagas Branahda Putra Agung; Maharani Ikaningtyas (Universitas KH. Abdul Chalim Mojokerto, 2025)
In the increasingly competitive fashion industry, companies need to develop appropriate strategies to increase product appeal and encourage consumer purchasing interest. Brand image, price, and marketing content are important factors that can influence consumer behavior in making purchasing decisions. This study aims to analyze the influence of brand image, price, and marketing content on purchasing interest in Erigo products in Surabaya. This study uses a quantitative approach with a survey method. The population in this study was consumers who have purchased or are familiar with Erigo products in Surabaya. The sampling technique used was a purposive sampling method with 156 respondents. Data collection was carried out through the distribution of online questionnaires. The data analysis technique used was multiple linear regression to determine the effect of each independent variable on the dependent variable. The results of the study indicate that brand image, price, and marketing content partially and simultaneously have a positive and significant effect on purchasing interest in Erigo products in Surabaya. This finding reinforces the importance of managing a comprehensive marketing strategy in increasing the competitiveness of local brands amidst the dynamic competition in the fashion market.